Preparation of empty fruit bunch as a feedstock for gasification process by employing hydrothermal treatment. (October 2018) - Hantoko, Dwi; Yan, Mi; Prabowo, Bayu; Susanto, Herri
Abstract: Experiments were carried out in a 500 mL digester at a temperature of 120, 150, or 180 o C for a holding time of 60 min. The ratio of water to empty fruit bunch was 8 mL/gram. At these HT process conditions, proximate analysis, ultimate analysis and heating value of HT-EFB (solid product from HT) did not change significantly. However, the ash content in HT-EFB decreased significantly even from HT with a temperature of 120 o C, from 3.20% to 1.9% for raw EFB to HT-EFB, respectively. Furthermore, K2 O content in the ash in HT-EFB decreased significantly also, i.e. from 24% to 17%. Concerning with potassium, a longer holding time (HT at 120 o C) could further decrease the potassium content in HT-EFB, from 16% to 9% for the holding time of 60 to 120 min, respectively. Since SiO2 dissolved very little in water while alkaline dissolved much more, silica content in the ash increased from about 44% in raw EFB to 53% in HT-EFB. In line with the change in the ash content and the mineral composition in the ash, the melting properties of ash in HT-EFB significantly changed.